Synthetic Sulfonate Additives for Lubricating Oils - Mammadova, P.Sh.; Veliyeva, S.M.; Gulaliyev, I.D. (Herald of Azerbaijan Engineering Academy, 2021)
Oil-soluble calcium sulfonates on the basis of alkyltetralin obtained using olefins of C20–C30 fraction are developed and characterized. The developed synthetic sulfonate additives with different alkalinity possess high physico-chemical and functional properties and are superior in performance to commercial oil sulfonates C-150 and C300, as well as foreign analogues – additives OLOA-246B and Hightech 6060M. Using the obtained high-alkaline additive, an experimental motor oil M-10Г2 was developed, which in terms of quality indicators meet the requirments.